On the Injection of Surfactant into the Turbulent Boundary Layer in Low Reynolds Number Flows - Siginer, D (American Institute of Physics, 2025)
The effect of slit injection of a surfactant solution on the flow characteristics of the boundary layer on a flat plate in low Reynolds number ( R e < 20 000 ) flows is studied experimentally. The velocity distribution at 10 and 20 times the injection slit width (Lc) away from the slit was measured by particle image velocimetry (PIV). The effects of the concentration and the injection flow rate of the polymeric solution on the flow characteristics of the boundary layer at low Reynolds numbers were discussed, through the comparison of the local velocity and velocity fluctuation at different surfactant concentrations and the injection velocity at the slit. Results show that within the studied concentration and injection velocity range, the drag reduction is greatest at a polymer concentration of 50 ppm. As the concentration increases, the drag reduction effect gradually decreases. Furthermore, the injection of the polymer solution has a certain suppressive effect on the turbulent kinetic energy of the boundary layer, especially the velocity fluctuations perpendicular to the wall. Appropriate injection concentrations can also suppress local Reynolds shear stresses in the boundary layer. © 2025 Author(s).